ESL Learning in the Public ECE Sector of Dhaka and Kolkata - Roy Chowdhury, Probal (Journal of Applied Linguistics, 2025)
This article aims to discuss the need for research in the field of ESL learning as a stand-alone area. What can be achieved by working in this area, its implications for the field of Applied Linguistics, and who would it benefit, is discussed in detail, as it has been explored using qualitative methodology that confusion still persists regarding difference between teaching, learning and acquisition, even among teachers. Even after the emergence of Educational Linguistics, within the wider realm of Applied Linguistics, where teaching and learning ought to receive equal importance, learning is still not given proper attention. Language and education planning and policymaking prioritize the needs of the education system and its deliverables rather than the needs of an efficient learning environment. The whole study is based on a comparative case study design. Respondents were found still unable to distinctively explain teaching, learning and education in Dhaka and Kolkata. Dhaka is the national capital of Bangladesh. Kolkata is an Indian city and the capital of West Bengal State. In this article the reader will be able to explore why ESL learning in the early childhood period should be taken more seriously as a stand-alone area of research, especially where English is taught as a second language, like in Dhaka and Kolkata. Pupils of Dhaka and Kolkata both share a common first language that is Bengali, which they start learning together with ESL. Data from both the cities were collected and analyzed at the same time.   Keywords : ESL; Early Childhood Education; Language Teaching; Language Policy; Public Education